Contextualization of the Concept of 'Antaradlin' as a Legal Guarantee of On-Line Buying and Selling Transactions - Eva Andriani; Arifatul Ma'ani; Syovinatus Sholicha (International Journal Labs, 2023)
'Between the meaning of voluntary being an important part of the practice of buying and selling, practically there must be a marker that proves that both parties are equally willing in a transaction the marker is called a contract in the form of a certain shigat. Thus, the interadlin principle, is really rated abash. Over time that is always developing, buying and selling online becomes a solution that greatly facilitates the practice of buying and selling, on the other hand online media is also the culprit of fraud. Therefore, in the current context, the principle between adlin and its provisions must be contextualized with the current era. So with a rule that reads